2022
DOI: 10.3390/ijms23062943
|View full text |Cite
|
Sign up to set email alerts
|

A Role of Complement in the Pathogenic Sequelae of Mouse Neonatal Germinal Matrix Hemorrhage

Abstract: Germinal matrix hemorrhage (GMH) is a devastating disease of infancy that results in intraventricular hemorrhage, post-hemorrhagic hydrocephalus (PHH), periventricular leukomalacia, and neurocognitive deficits. There are no curative treatments and limited surgical options. We developed and characterized a mouse model of GMH based on the injection of collagenase into the subventricular zone of post-natal pups and utilized the model to investigate the role of complement in PHH development. The site-targeted comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…Our patient with the MASP-1 variant Ala544Thr had severe and persistent diffuse gastrointestinal bleeding leading to ICU-admission twice and ending up being lethal. Massive haemorrhage is thought to be a possible trigger of complement activation ( 47 , 48 ) and activated complement could contribute to tissue damage seen at the site of the haemorrhage ( 49 , 50 ). We speculate that the MASP-1 variant rs1712360640 with severe GI-bleeding could lead to a more vigorous activation of the complement and coagulation cascade, leading to endothelium-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient with the MASP-1 variant Ala544Thr had severe and persistent diffuse gastrointestinal bleeding leading to ICU-admission twice and ending up being lethal. Massive haemorrhage is thought to be a possible trigger of complement activation ( 47 , 48 ) and activated complement could contribute to tissue damage seen at the site of the haemorrhage ( 49 , 50 ). We speculate that the MASP-1 variant rs1712360640 with severe GI-bleeding could lead to a more vigorous activation of the complement and coagulation cascade, leading to endothelium-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we demonstrated that complement inhibition reduced C3-dependent microglial phagocytosis of neurons and reduced inflammation at early timepoints after GMH [ 29 ]. Here we have followed outcomes chronically and show a role for the terminal complement activation product, the MAC, in early GMH pathogenesis and which appears to impact chronic pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Animal breeders and litters were randomly assigned to each of the three groups. A single individual performed all surgeries and treatments, and all GMH injuries were performed by guided injection of collagenase into the subventricular zone (SVZ) on postnatal day 4 (P4), as previously described [ 29 ]. Testing and scoring were blinded to group randomization for the duration of the study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations